Enhancing construction excellence: The role of Green Human Resource Management (GHRM) in organizational performance - Zarith Sufia, Azlan; Tuan Hasmira, Tuan Hussain (Penerbit Universiti Malaysia Pahang, 2025)
Integrating environmental management practices is crucial for mitigating the construction industry’s environmental impact. Environmental management in the construction industry involves implementing practices and policies designed to reduce the environmental impact of construction activities. Green Human Resource Management (GHRM) is important in ensuring that environmental management practices are effectively implemented and maintained. The studies exploring the connection between organizational performance and GHRM, especially among construction organizations, are still underutilized. Therefore, this study will investigate the construct of GHRM and analyze the relationship between GHRM’s construct and organizational performance among construction companies focused in Pahang State, Malaysia. The quantitative research method was utilized, and SPSS ver.23 and Smart PLS 4.0 software were applied to test the measurement and structural models of this study. The findings revealed that green recruitment and selection, green training and development, green performance management, and green reward and compensation are positively associated with organizational performance. The findings of this study also reveal that the respondents were aware of the significance of GHRM practices, however, their level of understanding of the issues was constructed through experience, and not based on any framework, standards, or other formal instruction/documentation.